Three Phase Sinusoide Output Voltage of Multi Carrier for Nine Level Cascade H-Bridge Inverter with DC Fuel Cell - setiyono setiyono (Majalah Ilmiah Teknologi Elektro, 2025)
This paper discusses a cascade inverter 9 three-phase power system using a Cascade H Bridge inverter type with a DC Fuel Cell voltage source. The goal is to reduce the Total Harmonic Distrotion (THD) content in the output waveform in accordance with IEEE 519 standards below 5%. At each level the inverter is supplied by the fuel cell as a DC source and in series with the next level inverter circuit to get 9 output voltage levels. The switch performance of each level is controlled by PWM pulses at the level of different amplitudes but the same frequency. Unlike conventional approaches that rely solely on low-level inverters or fixed DC sources, this study proposes the implementation of a nine-level cascade H-Bridge inverter topology powered by a DC fuel cell with three-phase multi-carrier modulation technique to produce high-quality sinusoidal voltage. This system shows increased efficiency, harmonic reduction, and more optimal utilization of green energy. Simulation results show that the output voltage form of each phase inverter is a 9-level ladder wave with a THD of 13.67%. By installing a low pass filter, the output voltage waveform changes to sinusoidal with and THD can be reduced to 2.92%. The power system with this THD value can still be tolerated to occur in an electric power system